Improving Science Skills Through The Experiment Method Of Making Toge From Green Beans In Group B Children (In The Smart Paud Unit, Suka Bulan Village, Seluma Regency) - Novanda Rahmadani, Dhea (Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine whether through the experimental method of making bean sprouts from mung beans can improve science skills in group B children at the Smart PAUD Unit in Suka Bulan Village, Seluma Regency. This type of research is PTK which is focused on the classroom situation and the procedures used are cyclical. The subjects in this study were group B children totaling 15 children. This classroom action research uses the John Elliot model where each cycle consists of four activities, namely planning, implementation, observation, and reflection carried out through two cycles. Data collection techniques used observation and documentation methods. Data analysis was carried out descriptively qualitative-quantitative with the emphasis used to determine the improvement of the process expressed in a predicate, while quantitative data analysis was used to determine the improvement of results using percentages. The results of improving science skills through the experimental method of making green beans in group B children in cycle I were 72% and in cycle II an increase of 89% was found. The conclusion of the research is that through the experimental method of making green beans can improve science skills in group B children at PAUD Smart Suka Bulan Village, Seluma Regency. Evidently in cycle II there was an increase, the percentage of achievement was 89% with very good developing criteria (BSB).